Continuing Education: construction of knowledge and educational strategies by oncology nurses - Fabiana Cristina dos Santos; Ana Maria Laus; Andrea Bernardes; Silvia Helena Henriques Camelo (Universidad de Alicante, 2018)
Objective: Characterize the permanent training strategies developed by oncology nurses working in hospitals. Methodology: This is an exploratory study, a qualitative approach, and the methodological design the multiple case study. This research was performed in Oncology Units of two Teaching Hospitals and 30 nurses participated. To collect data used semi-structured interviews and data analysis was performed using thematic analysis. Results: Strategies of education provided by the hospitals are pre-employment training, courses and scientific meetings, on various subjects, not being reported specific preparation in the area of oncology causing the professionals in these units, seek for specialized institutions in order to meet their professional development as necessary for his performance skills. As the strategies of education performed by nurses highlights the practical teaching from the routines of the service. Conclusion: This study will help nurses reflect on their practice considering the comprehensiveness of care provided to cancer patients, defining new modes, mechanisms and instruments for in-service training. Thus as institutions favor the training of these professionals using updated teaching strategies in this sector.